Habibie, Soeharto, dan Islam - Husaini, Adian 1965- (Gema Insani Press, 1996)
Political issues in Indonesia related to B.J. Habibie, b. 1936, State Minister of Research and Technology, Soeharto, b. 1921, president of Indonesia, and ICMI, All-Indonesia Association of Moslem Intellectuals